2018
DOI: 10.1186/s40545-018-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Access to innovative cancer medicines in a middle-income country - the case of Mexico

Abstract: BackgroundCancer has become the third cause of death in Mexico. Treatment for cancer is often complex and lengthy. New and better medicines enter the market at high prices, which may limit access. Like most Latin American countries, Mexico has an essential cancer medicines list that includes innovative medicines. Their accessibility and use in the public sector remains unknown. Therefore, we describe the use, as a proxy of access, of innovative and essential cancer medicines in the public sector in Mexico, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Overall, 13 studies were included in the review with some having multiple outcomes: five studies (16)(17)(18)(19)(20) were on the pricing of anticancer medicines, four studies (4,18,21,22) addressed affordability of anti-cancer medicines, and five studies reported (8,18,20,22,23) on the availability of anticancer medicines and overall four studies (8,(24)(25)(26) was on access to anti-cancer medicines.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 13 studies were included in the review with some having multiple outcomes: five studies (16)(17)(18)(19)(20) were on the pricing of anticancer medicines, four studies (4,18,21,22) addressed affordability of anti-cancer medicines, and five studies reported (8,18,20,22,23) on the availability of anticancer medicines and overall four studies (8,(24)(25)(26) was on access to anti-cancer medicines.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (8,(24)(25)(26) demonstrated that barriers to access and use of innovative cancer medicines are linked to the limited coverage of public insurance schemes (26), non-inclusion in the EML ( 24), non-availability of the medicine at the facilities, and updated clinical guidelines (24)(25)(26). The innovation field for anticancer medicines is growing (36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations